2012
DOI: 10.1183/09031936.00014012
|View full text |Cite
|
Sign up to set email alerts
|

Smoking cessation strategies in patients with COPD

Abstract: Smoking cessation is the cornerstone of treatment of chronic obstructive pulmonary disease (COPD) patients. This systematic review evaluates the effectiveness of behavioural and pharmacological smoking cessation strategies in COPD patients.MEDLINE was searched from January 2002 to October 2011. Randomised controlled trials evaluating the effect of smoking cessation interventions for COPD patients, published in English, were selected. The methodological quality of included trials was assessed using the Delphi l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(31 citation statements)
references
References 59 publications
0
31
0
Order By: Relevance
“…It was reported that counseling, pharmacotherapy treatments, and NRT are also effective (53,119,124,127,133). According to two independent systematic reviews by Warnier et al (135) and van der Meer et al (129), pharmacological and behavioral (psychosocial) intervention was more effective than no intervention. Furthermore, both of the reviews concluded that a combination of pharmacological and behavioral (psychosocial) intervention was more effective than each alone.…”
Section: Tobacco Treatment Strategies In Copd-targeting Stimulusmentioning
confidence: 99%
“…It was reported that counseling, pharmacotherapy treatments, and NRT are also effective (53,119,124,127,133). According to two independent systematic reviews by Warnier et al (135) and van der Meer et al (129), pharmacological and behavioral (psychosocial) intervention was more effective than no intervention. Furthermore, both of the reviews concluded that a combination of pharmacological and behavioral (psychosocial) intervention was more effective than each alone.…”
Section: Tobacco Treatment Strategies In Copd-targeting Stimulusmentioning
confidence: 99%
“…Smoking cessation is a critical component of the effective management of COPD. [11] Savings of disposable income, achieved by quitting smoking, would also be available for basic necessities, particularly for those living in poverty.…”
Section: Tobacco Smoking In South Africamentioning
confidence: 99%
“…It is also the only drug which has proven long-term efficacy in smokers with chronic obstructive pulmonary disease [394,395] and is efficacious for patients with psychiatric disorders [396]. The introduction of varenicline in the US appeared to coincide with a net overall increase in both aided and unaided attempts to quit smoking [40]; although a similar effect was not seen in the UK [57,397].…”
Section: Vareniclinementioning
confidence: 88%